Analisis Pemahaman Konsep Dan Kemampuan Pemecahan Masalah Matematika Pada Mata Kuliah Kalkulus Dasar - Syafa’atun Syafa’atun; Nurlaela Nurlaela (Jurnal Ilmiah Wahana Pendidikan, 2022)
This research is a qualitative descriptive study. The research subjects were second semester students of industrial engineering study program with a sample of 25 students. The data collection method used includes a student's mathematical understanding ability test in the basic calculus course. Based on the results of Key's research, the level of ability of Industrial Engineering students in basic calculus courses is as follows: (1) Students are able to complete integration with an achievement percentage of 75%. (2) Students are able to understand the concept of indeterminate forms and improper integrals and have an achievement percentage of 75%. (3) Students who are able to understand and are skilled in using infinite series formulas and methods to solve problems have an achievement percentage of 75%. (4) Students who are able to understand the concept of geometry in the field and space, so as to achieve the indicator obtained a percentage of 75%. (5) Students are able to understand concepts and are skilled in using formulas and derivative methods to solve the problem of achieving 50% indicators. (6) Students are able to understand concepts and are skilled in using double integral formulas and methods to solve problems, the indicator percentage achievement reaches 50%. (7) Students are able to understand concepts and are skilled in using formulas and ordinary equation methods to understand problems, the indicator percentage achievement reaches 50%. Analysis, Concept Understanding, Ability to solve mathematical problems